2019
DOI: 10.1111/medu.13898
|View full text |Cite
|
Sign up to set email alerts
|

Geo‐sociocultural influences on empathy

Abstract: Kelly and Easton reflect upon Ponnamperuma et al.'s investigation of the potential for regional variation in reports of empathy change during medical training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Empathy is related to the emotional response arising from the apprehension or understanding of the emotional state of the other, being an important factor for establishing interpersonal relationships and, therefore, particularly relevant in the doctor-patient relationship 8,9 . Studies have suggested that medical students' empathy may change throughout the course, ranging from a small increase to a decrease in it 10,11,12 . Interestingly, it has been observed that this skill tends to decrease exactly when medical students start the clinical activity in the undergraduate years 13,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Empathy is related to the emotional response arising from the apprehension or understanding of the emotional state of the other, being an important factor for establishing interpersonal relationships and, therefore, particularly relevant in the doctor-patient relationship 8,9 . Studies have suggested that medical students' empathy may change throughout the course, ranging from a small increase to a decrease in it 10,11,12 . Interestingly, it has been observed that this skill tends to decrease exactly when medical students start the clinical activity in the undergraduate years 13,14,15 .…”
Section: Introductionmentioning
confidence: 99%